Analisis Kesiapan Mahasiswa S2 Pendidikan Dasar Sebagai Guru Professional Dalam Memberikan Bimbingan Kepada Siswa - Maret Markus Harefa; Nidya Chandra Muji Utami; Erry Utomo (Jurnal Elementaria Edukasia, 2023)
Graduates of the Master of Basic Education are required to become professional teachers and be able to provide guidance services to elementary school students. This research with the type of explanatory sequential mixed methods aims to see the readiness of Master of Basic Education students in providing guidance services to elementary school students. This research was conducted in semester 117 of the 2022/2023 academic year with 27 respondents of Master of Basic Education students in 2022 who have worked as professional elementary school teachers. The research sample was determined by purposive sampling method. The research data were collected and analyzed using qualitative and quantitative approaches from research instruments in the form of semi-structured interviews and semi-structured questionnaires. The research findings show that the level of readiness of respondents in providing nine types of guidance services to elementary school students is in the percentage range between 82% and 93%. This means that the level of readiness of Master of Basic Education students as professional elementary school teachers in providing guidance services to elementary school students is very good.